Development Of Cellulose-based Films Containing Salicylic Acid For Wound Dressing Applications: Fabrication, Properties And In Vitro Assessment - Mohd Ibnu Haikal Ahmad Sohaimy; Muhammad Amir Amzar Ismail; Azwani Sofia Ahmad Khiar; Norizah Mhd Sarbon; Nora Salina Md Salim; Hanis Nadia Yahya; Mohd Ikmar Nizam Mohamad Isa (Sage Journals Home, 2024)
Indexed by WOS/Scopus/ERA